Dual-Band Eight-Element MIMO Array Using Multi-Slot Decoupling Technique for 5G Terminals - Wei Hu; Long Qian; Steven Gao; Le-Hu Wen; Qi Luo; Hang Xu; Xuekang Liu; Ying Liu; Wei Wang (IEEE Access)
This paper presents a dual-band eight-element multiple-input multiple-output (MIMO) array using a multi-slot decoupling technique for the fifth generation (5G) mobile communication. By employing a compact dual-loop antenna element, the proposed array obtains two broad bandwidths of 12.2% and 15.4% for sub-6GHz operation. To reduce the mutual coupling between antenna elements, a novel dual-band decoupling method is proposed by employing a multi-slot structure. The proposed MIMO array achieves 15.5-dB and 19.0-dB isolations across the two operating bands. Furthermore, three decoupling modes generated by different bent slots can be independently tuned. Zero ground clearance is also realized by the coplanar arrangement of the antenna elements and decoupling structures. The proposed MIMO array was simulated, fabricated, and measured. Experimental results agree well with the simulations, showing that the dual-band MIMO array has good impedance matching, high isolation, and high efficiency. In addition, the envelope correlation coefficient and channel capacity are calculated and analyzed to validate the MIMO performance of the 5G terminal array. Such a dual-band high-isolation eight-element MIMO array with zero ground clearance is a promising candidate for 5G or future mobile applications.